2022
DOI: 10.3390/ijms232113260
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Molecular Pathophysiology: Acetylation of Repurposing Drugs

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) induces immune-mediated type 1 interferon (IFN-1) production, the pathophysiology of which involves sterile alpha motif and histidine-aspartate domain-containing protein 1 (SAMHD1) tetramerization and the cytosolic DNA sensor cyclic-GMP-AMP synthase (cGAS)–stimulator of interferon genes (STING) signaling pathway. As a result, type I interferonopathies are exacerbated. Aspirin inhibits cGAS-mediated signaling through cGAS acetylation. Acetylation cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 130 publications
0
17
0
Order By: Relevance
“…We de ne this up-regulation as acquired Mendelian up-regulation. NRP1 + ILC3s constitute the in ammatory cascade pathway with IFN1 or cGAS-STING through acetylation-deacetylation 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We de ne this up-regulation as acquired Mendelian up-regulation. NRP1 + ILC3s constitute the in ammatory cascade pathway with IFN1 or cGAS-STING through acetylation-deacetylation 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Immune-to-brain communication occurs as glia, microglia, and astrocytes interpret and propagate in ammatory signals, in uencing physiological and behavioral changes 55 56 . In addition, activating the peripheral immune system affects physiological and clinical responses by the immunological memory engram pathway 9 . Jacqueline et al reported a relatively high incidence of cognitive impairment in processing speed, category uency, executive functioning, memory encoding, and recall several months after hospitalization in COVID-19 patients.…”
Section: The Cgas-sting-ifn-i Axis In Ad Pathogenesis By Vrdsmentioning
confidence: 99%
“…The recognized pathways invade the brainstem and involve transsynaptic transfer via peripheral, olfactory, or cranial nerves (Fig. 3) 41 .…”
Section: The Neuropilin-1 Pathwaymentioning
confidence: 99%
“…Whether amyloid microclots could explain the elevated amyloid beta-42(Aβ-42) and amyloid beta-40 (Aβ 40) serum levels reported in chronic obstructive pulmonary disease patients [ 158 , 159 ] and the link with mild cognitive decline (MCI) is debatable. Other attempts to address some of the multiple pathogenic mechanisms (multiple organ dysfunction (MOD) and acute respiratory distress syndrome (ARDS)) also involve aspirin and dapsone [ 160 ]; the latter considered a second-line treatment of immune thrombocytopenia [ 161 ] and linked to the regulation of mild cognitive impairment (MCI) in Alzheimer’s disease (AD) [ 162 ].…”
Section: Diarylamidines Serine Proteasesmentioning
confidence: 99%